Emergency department use by persons with MS: A population-based descriptive study with a focus on infection-related visits. (October 2022) - Graf, Jonas; Ng, Huah Shin; Zhu, Feng; Zhao, Yinshan; Wijnands, José MA; Evans, Charity; Fisk, John D; Marrie, Ruth Ann; Tremlett, Helen
We described emergency department (ED) visits (all visits and infection-related) by persons with multiple sclerosis (MS) in British Columbia, Canada (1 April 2012 to 31 December 2017). We identified 15, 350 MS cases using health administrative data; 73.4% were women, averaging 51.4 years at study entry. Over 4.9 years of follow-up (mean), 56.0% of MS cases visited an ED (mean = 0.6 visits/person/year; total = 37, 072 visits). A diagnosis was documented for 25, 698 (69.3%) ED visits, and 18.4% (4725/25, 698) were infection-related. Inpatient admissions were reported for 20.4% (5238/25, 698) of all and 29.2% (1380/4725) of infection-related ED visits. Findings suggest that the ED plays a substantial role in MS healthcare and infection management.